Small Business Lending and Bank Profitability - James Kolari; Robert Berney; Charles Ou (Journal of Entrepreneurial and Small Business Finance, 1996)
In theory commercial banks exist to resolve asymmetric information problems in credit markets. Because small business firms have much greater information problems than large firms, it is not surprising that they depend almost entirely on banks for external finance needs. Unfortunately, little is known either in academic literature or banking practice about the profitability of small business credit (and related information) services. The present study employs recently available business loan size information from the Call Reports for all insured U.S. commercial banks in 1994 and 1995 to examine the relationship between bank profits and small business credit. Regression analyses are conducted using the rate of return on assets and business loans less than 250,000, in addition to a number of variables that proxy various dimensions of risk that potentially could influence this relationship. Due to the fact that small and large banks differ considerably in their lending activities, separate analyses are conducted for five asset size groups. In brief, we find that, while small business loans likely have a negligible effect the profits of large banks, they tend to increase the profitability of small banks over time, holding constant various bank risk characteristics.
Keywords: L25; G21; G32; 650; Bank; Lending; Small business Lending; Borrowing; Bank Profitability; Profitability